Observations of Breaking Internal Tides on the Australian North West Shelf Edge - Lauton, Gustavo; Pattiaratchi, Charitha Bandula; Lentini, Carlos A. D. (Frontiers in Marine Science, 2021)
A comprehensive observational data set was used to examine shoreward propagating semidiurnal internal tides as they shoal, break and run-up as turbulent boluses across the edge of the Australian North West Shelf (NWS), offshore Dampier, during late winter 2013. The measured waveforms and wavefields supported the grouping of events into two distinct categories: (1) prior-; and, (2) post- wave breaking. It was found that the transition from (1) to (2) was marked by the rise of nonlinear steepening (α) and reduction in dispersion (β), both coefficients that parameterize nonlinear wave effects on the Korteweg-de Vries (KdV) equation. We introduced a criterion for wave breaking from the dimensionless parameter (δ) that relates these two terms: wave breaking occurs when δ<1. In the first group, dispersive effects were dominant to spread energy out of the semidiurnal wave to a dispersive wave packet of short-period internal solitary waves (ISWs). In the second, dispersion was considered small compared to the cumulative effect of nonlinear steepening. Here, the semidiurnal wave built sufficient energy at its rear face to generate wave breaking, which has been known to produce multiple turbulent boluses. Similar observations have not been described for this region during winter months and highlight that the nonlinear internal wave field is an important feature on the NWS throughout the year. Additionally, measurements obtained through autonomous ocean glider profiles revealed some of the post-breaking characteristics that included intensive vertical mixing and transport of dense water and suspended material onshore of the shelf break.